Detection of spontaneous anti-neoepitope T-cell responses in non-metastatic bladder cancer patients - Brochier, Walther; Nguyen, Sylvain; Cesson, Valérie; Bricard, Orian; van Baren, Nicolas; Hames, Gérald; Dauguet, Nicolas; Dano, Hélène; Tombal, Bertrand; Rodrigues-Dias, Sonia-Cristina; Masnada, Audrey; Genolet, Raphael; et al. (Frontiers in Immunology, 2025)
BackgroundBladder carcinomas are immunogenic, and patients with bladder cancer benefit from immune checkpoint therapy. This is correlated to a high tumor mutation burden, which provides a higher number of neoepitopes that can be recognized by tumor-specific CD8+ T cells. Intravesical Bacillus Calmette-Guérin (BCG) is used to treat non-muscle invasive bladder cancer (NMIBC), but its mechanism of action remains elusive. Most lymphocytes appearing in the urine of BCG-treated patients are CD4+ T cells though preclinical studies showed that CD8+ T cells are also necessary for BCG treatment efficacy. It is currently unknown which proportion of patients with non-metastatic bladder cancer develop a spontaneous antitumor CD8+ response, and if BCG treatment influences this response.MethodsIn a first cohort of 15 NMIBC and 9 muscle invasive bladder cancer patients, we used IFN-y ELISPOT assays to screen for the presence of anti-neoepitope CD8+ T cells in the blood, tumor and urine. In a second cohort of 4 NMIBC patients, we analyzed the features and specificity of CD8+ T cells infiltrating the tumoral or bladder tissues before and after BCG using single cell transcriptomic analyses. A total of 31 tumor-infiltrating CD8+ clonotypes were screened against neoepitopes and tumor cDNA libraries.Results9 out of 24 patients from the first cohort mounted a spontaneous and functional anti-neoepitope T-cell response in blood and/or tumor. In 5 patients from this cohort who were treated with BCG, no neoantigen-specific T cells were detected in urine during treatment. In the second cohort, 6 out of 6 TCRs from exhausted CD8+ TILs from one patient recognized 5 different neoepitopes. T-cell receptor (TCR) repertoire analyses indicated that the frequencies of these tumor-specific T cells did not increase after BCG instillations, neither in the bladder nor in the blood. None of the 25 other TCRs of CD8+ T cells recognized tumor-specific antigens.ConclusionsWe show that one third of patients with non-metastatic bladder cancer mount a spontaneous and functional anti-neoepitope CD8+ T-cell response detectable in blood or tumor. In 4 patients with NMIBC, BCG treatment did not boost or induce the anti-neoepitope response, suggesting alternative mechanisms of action for its efficacy.